ENHANCING SHORT STORY WRITING SKILLS THROUGH PROJECT-BASED LEARNING AMONG GRADE VI STUDENTS OF SDN 52 LUBUKLINGGAU - Rahman Aditiya (CV Grasta Glory, 2025)
Writing short stories is a crucial component of language learning, fostering students' creativity, imagination, and communication skills. However, many students still struggle to express ideas effectively in writing due to passive learning methods and limited engagement. This research aims to determine the effectiveness of the Project-Based Learning (PjBL) model in improving the Indonesian language learning outcomes, specifically in creative short story writing skills among Grade VI students at SDN 52 Lubuklinggau. This Classroom Action Research involved 30 students (16 boys and 14 girls) and was conducted over three cycles, each comprising planning, implementation, observation, and reflection stages. Data were collected through tests, observation, and documentation, and analyzed both qualitatively and quantitatively. The results showed a consistent improvement in students’ writing performance across cycles. Students demonstrated better idea development, narrative structure, and creativity. In conclusion, the application of the Project-Based Learning model significantly improved students’ Indonesian language learning outcomes, particularly in writing creative short stories. The model proved to be an effective, student-centered approach that encouraged active participation, collaboration, and real-world relevance in learning. It is recommended that educators apply PjBL in other language learning contexts to further explore its potential in enhancing literacy skills. Future research may examine long-term effects of this model on students’ writing motivation and independence.